The Multicultural Values of the Huma Betang Philosophy as a Foundation for Character Building in Elementary School Students - Sion, Holten; Affandi, Muhamad (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
Life within Huma Betang teaches the importance of accepting and respecting differences, maintaining harmony, and prioritizing the common good over personal interests. Elementary education, as the foundation of character building, plays a strategic role in instilling the multicultural values embodied in the Huma Betang philosophy. The limited literature and scholarly studies discussing the implementation of multicultural values based on local culture in elementary school settings, particularly those focusing on Huma Betang, represent a gap that needs to be addressed through research and curriculum development. This study was conducted using a qualitative approach with a phenomenological method to observe the cognitive and character changes experienced by students through their interactions with learning components explored in their natural form. The findings of this study indicate that the multicultural values of the Huma Betang philosophy, such as tolerance, togetherness, mutual cooperation, and mutual respect, have been effectively implemented in shaping the character of students at SDN 6 Bukit Tunggal, Palangka Raya. These values are not only applied in non-academic activities like mutual cooperation but also in students' daily interactions, creating a harmonious atmosphere amid cultural diversity.